2018
DOI: 10.2340/16501977-2284
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with upper leg muscle strength in knee osteoarthritis: A scoping review

Abstract: Lower muscle quality, physical inactivity, more severe joint degeneration, and higher pain are reported to be associated with lower strength in the upper leg muscles in knee osteoarthritis. Future research into knee osteoarthritis should focus on other potential determinants of muscle strength, such as muscle quantity, muscle activation, nutrition and vitamins, and inflammation. In hip osteoarthritis, more research is needed into all potential determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 84 publications
(255 reference statements)
1
22
2
Order By: Relevance
“…Recent studies have shown that expression of mTOR is increased in peripheral blood mononuclear cells of OA patients, and is related to disease activity, 31 and that pharmacological inhibition or genetic deletion of mTOR in chondrocyte decreases the severity of OA in an animal model. 16,32 However, whether or not mTORC1 is activated in subchondral bone, and its role in OA has not been reported. Western blot analysis of subchondral bone tissues from collected tibial plateau specimens showed an enhanced phosphorylation of S6 (S235/236) (p-S6, a target and marker of mTORC1 activation) in OA patients compared to that of control (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that expression of mTOR is increased in peripheral blood mononuclear cells of OA patients, and is related to disease activity, 31 and that pharmacological inhibition or genetic deletion of mTOR in chondrocyte decreases the severity of OA in an animal model. 16,32 However, whether or not mTORC1 is activated in subchondral bone, and its role in OA has not been reported. Western blot analysis of subchondral bone tissues from collected tibial plateau specimens showed an enhanced phosphorylation of S6 (S235/236) (p-S6, a target and marker of mTORC1 activation) in OA patients compared to that of control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12 Indeed, homeostasis and integrity of articular cartilage rely on its biochemical and biomechanical interplay with subchondral bone and other joint tissues, 13 and treatment targeting articular cartilage alone in OA has proven to be insufficient to halt disease progression. In a situation of instability, such as occurring with ligament injury, 14 excessive body weight, 15 or weakening muscles related to aging, 16 the mechanical loading on weight-bearing joints is dramatically increased, and changes in the subchondral bone microarchitecture may precede articular cartilage damage. Thus, changes in the subchondral bone have been suggested to predict the severity of cartilage damage in OA.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to measures of maximal force or strength measured using instruments such as dynamometers, where there is unlimited time for recruitment of motor units and optimal engagement of muscle filaments, which may therefore not detect slowing of these components. This slowing is well documented with regards to aging [21], and there is growing evidence of similar processes occurring in osteoarthritis [3]. This reinforces the importance of measures of muscle power which include velocity, to detect early changes in neuromuscular function.…”
Section: Discussionmentioning
confidence: 67%
“…Muscle weakness is a recognised feature of osteoarthritis, with reports of 20-40% weaker quadriceps in knee osteoarthritis patients compared with age-matched controls [3]. Proposed mechanisms behind this relationship include the role of these muscles in stabilising the joint and as shock absorbers, to reduce joint loading and muscle weakness is also associated with worsening pain and physical function [4].…”
Section: Introductionmentioning
confidence: 99%
“…OA patients have pain related to joint degeneration, inflammation and joint stiffness that reduce range of motion [4][5][6][7]. These disabilities can combine with depressive states and expose them to a negative spiral of accumulation of negative effects due to sedentary lifestyle [8][9][10][11]. Such disuse atrophy of muscle is associated with ectopic adipogenesis and loss of knee muscle strength with limited flexion range [4].…”
Section: Introductionmentioning
confidence: 99%